REVOLUTIONIZING GRAPHIC DESIGN: THE SYNERGY OF AI TOOLS AND HUMAN CREATIVITY - Das, Subrato; Rani, Poonam (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Over the last few years, the rapid development of artificial intelligence has initiated new opportunities offered to designers. In the area of graphic design, multiple AI tools are available that enable users to benefit from the capabilities of this technology. Currently, illustrators, photographers, web designers, and other visual creators may use AI-driven applications and support to enhance the quality and variety of their works. Not only does this process help save a lot of time, but it also opens a variety of creative opportunities that one would not have thought of without technology. Human designers’ role becomes curator and directional advisor which puts more emphasise to strategy and visual creativity. One of the proposals is to figure out the ethical rules, revaluate existing education, and somehow make sure that human kind is protected. The future picture is the AI and human creativity complementing each other, to create new innovations in the field of design.